RISING ADMISSION TRENDS IN EMERGENCY DEPARTMENT. IS IT THE RIGHT TIME TO ADOPT THE NEW MODEL OF ACUTE MEDICAL UNIT? - Zaman, Qazi Nayyar (Journal of Postgraduate Medical Institute, 2018)
In the last two decades there has been a significant change and improvement in the delivery mode of acute care and in the team that delivers it. With the introduction of acute physicians at the forefront as well as unscheduled care has shown a significant reduction in length of hospital stay, readmission rates and risk of mortality. Acute medicine is a relatively new specialty that is evolving rapidly. Because of its crucial role, it is expected to become a key player for the provision of healthcare in future. Acute medicine is one of the most versatile medical specialties. It is a sub-branch of internal medicine related to the early and immediate treatment of adult emergency patients by acute physicians.